Akibat Hukum Terhadap Penarikan Kembali Harta Yang Di Hibahkan Menurut KUH Perdata - Rizal Bobihu; Weny Almoravid Dungga; Mohamad Taufiq Zulfikar Sarson (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
A grant is the gift of an item to someone where the giver is still alive. Materially, the existence of a grant has something to do with inheritance. In contrast to a will, a grant is a lifetime expenditure of assets based on affection for the benefit of a person or for the benefit of a social, religious, scientific body, also to someone who has the right to be his heir. The purpose of this study is to find out the law on the withdrawal of donated assets according to the Civil Code, to find out the legal consequences of withdrawing donated assets according to the Civil Code, and to find out the settlement of the withdrawal of donated assets according to the Civil Code. The research conducted is legal research which is descriptive analysis in nature and uses normative juridical research. Through descriptive research, researchers try to describe events and events that are the center of attention without giving special treatment to these events. This study uses secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. Based on the results of the research it is understood that the withdrawal of gift items according to the Civil Code is regulated in article 1688 which reads that a grant cannot be revoked and therefore cannot be revoked, except in 3 cases, namely if the grantee's conditions are not met, if the person who was given the gift is guilty of committing or participating in an attempt to kill or some other crime against the donor himself, and if the grantor falls into poverty while the one who was given the gift refuses to provide for him. If the recipient of the grant refuses to provide a living or allowance to the grantor, after that the grantor falls into poverty. With the withdrawal or elimination of this gift, all kinds of items that have been donated must be returned to the grantor in a clean condition of the burdens attached to the item. The legal consequence of the decision to cancel a grant that has permanent legal force is that the object of the dispute, namely land, will return to the grantor and their rights. If the object of the dispute has been certified on behalf of the recipient of the grant, then with this decision the certificate becomes null and void.